Uruguay : Statistical Annex. (IMF Staff Country Reports; Country Report ;, 1995)
This paper describes the social security system and pension reform in Uruguay. The reform of the social security system is the most important structural issue facing Uruguay. Large social security outlays have led to high rates of payroll taxes and large transfers from the Central Government, which has encouraged tax evasion and reduced the availability of resources for other essential public outlays, such as investment and other social services. Moreover, the fast growth of social security outlays has threatened the solvency of the public finances, undermined confidence, and discouraged private investment.